Kajian Konsep Perancangan Rumah Sakit Ibu Dan Anak (RSIA) Kelas B di Kota Palangka Raya - Dennis Sandy Laurentius Situmorang (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Palangka Raya City, as the capital of Central Kalimantan Province, continues to experience an increasing population from year to year. With the increasing birth rate and the increasing population of children, the need for special health facilities for mothers and children is very necessary. Based on data from the Central Statistics Agency (BPS) of Palangka Raya City, it shows a significant increase in cases of Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). In 2023, there were 4 cases of MMR and 62 cases of IMR, while in 2022 there were only 2 cases of MMR and 9 cases of IMR. This indicates the need for special attention to maternal and child health services. The Maternal and Child Hospital (RSIA) plays an important role in providing special health services for mothers and children, including care during pregnancy, childbirth, postpartum, and care for newborns and children. This facility is crucial in ensuring patient health and safety. To overcome this problem, a RSIA with a higher classification is needed, namely class B type. This health facility is expected to be able to accommodate all forms of referrals from various districts around Palangka Raya and provide more comprehensive, quality health services, and is supported by a comfortable design for patients, especially for maternal and child health.